The Guided Inquiry Method on Learning Science for Children with Hearing Impairment - Niky Dewi Karunia Mariana; Ahmad Samawi; Sihkabuden Sihkabuden (Department of Special Education, 2018)
A guided inquiry method emphasizes the process of searching for and finding the answers to the problem. The purpose of this method is to help students to develop intellectual discipline, use smartphones to facilitate the delivery of material that cannot be explained by theory alone but it needs illustrations. This study uses the quantitative method of one group pretest posttest. Data collection is conducted by observation and interview, then analyzed with Wilcoxon. The results of this study indicated that the value before treatment was 38.14 and after giving the treatment was 83. The conclusion is that there is effect of using the guided inquiry method through the use of smartphones on the outcomes of learning science.